2020
DOI: 10.1210/clinem/dgaa839
|View full text |Cite
|
Sign up to set email alerts
|

Update on PCOS: Consequences, Challenges, and Guiding Treatment

Abstract: Polycystic Ovary Syndrome (PCOS) is one of the most common reproductive endocrine disorders in women and despite this, diagnostic challenges, delayed diagnosis and less than optimal treatment regimens plague the condition. The International PCOS network, consisting of geographically diverse international experts in PCOS as well as consumers, engaged in a multi-year international evidence-based guideline development process that was jointly sponsored by the European Society for Human Reproduction and Embryology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
179
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(251 citation statements)
references
References 102 publications
2
179
1
5
Order By: Relevance
“…Polycystic ovary syndrome (PCOS) is one of the most common gynecological disorders associated with fertility difficulties, and it affects 5-25% of all adolescent and reproductive-aged women across multiple geographic ancestries and ethnicities [1][2][3]. It has a multifactorial etiology and is characterized by reproductive dysfunction accompanied by metabolic abnormalities, and women with PCOS have an increased risk for pregnancy-related complications [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is one of the most common gynecological disorders associated with fertility difficulties, and it affects 5-25% of all adolescent and reproductive-aged women across multiple geographic ancestries and ethnicities [1][2][3]. It has a multifactorial etiology and is characterized by reproductive dysfunction accompanied by metabolic abnormalities, and women with PCOS have an increased risk for pregnancy-related complications [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle interventions leading to 5-10% weight loss may reverse anovulatory status, thereby increasing natural conception rates [1,4]. Moderate weight loss may also improve insulin resistance, dyslipidemia, and androgen excess in PCOS [5].…”
Section: Introductionmentioning
confidence: 99%
“…As we all know, Polycystic ovary syndrome (PCOS) is a highly heterogeneous endocrine disorder characterized by hyperandrogen, rare ovulation and polycystic ovary, and its pathogenesis is debated [14][15][16] .Previous studies have demonstrated that the core etiology and primary endocrine characteristics of PCOS are insulin resistance (IR) and hyperandrogenemia (HA), and they can interplay each other leading to metabolic syndrome, especially dyslipidemia [17][18][19][20][21] . AMH are often used as clinical observation indicators reflecting the ovarian reserve 22,23 , and the LH/FSH and T levels were significantly higher in PCOS patients compared with control patients 24,25 .Compared with those characteristics related to PCOS, the expression level of ANGPTL4 in ovarian GCs might be a independent factor which affected incidence of PCOS and could serve as a new predictor for PCOS according to results of ROC cure and binary logistic regression analysis.…”
Section: Discussionmentioning
confidence: 99%